Factores y variables asociadas al rezago en estudiantes de la Universidad de la Costa (2020)
Lag is one of the main problems of higher education worldwide, the Higher Education Institutions, have worked to strengthen their internal and external processes in search of the quality that generates permanence in university students and thus leads them to fulfill the objective of being professionals; Therefore, the permanence, graduation, good time management of the academic career become topics of interest for the development of quality education. Due to this problem, it gave us the reason why this research project aims to determine the factors and variables associated with lag in the students of the University of the CUC coast, in this study we proposed to determine those factors that are most associated, taking as a sample students who started in 2015-1 and until 2019-1 were in a backward condition for not having 90% of their credits approved. The results confirm the joint impact that individual, socioeconomic, academic and institutional factors have on university lag.